KEANEKARAGAMAN JENIS BURUNG (AVES) DI AREA SAWAH KOTA MATARAM, NUSA TENGGARA BARAT - Nurmayani, Nurmayani; Azima, Moh Fauzan; Yuliana, Yana; Zulhariadi, Muhammad (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2025)
In the midst of urban expansion in Mataram City, West Nusa Tenggara, bird diversity in rice field habitats is threatened with extinction, even though rice paddies play an important role as ecological corridors that support opportunistic species such as Passeriformes in controlling pests and maintaining the balance of agricultural ecosystems. This study identified and analyzed bird communities (Aves) in the BTN Kopajali rice field area and the Ring Road in April-May 2025, using direct observation methods in three plots per location, as well as analysis of Shannon-Wiener (H'), dominance (C), importance value (INP), and evenness (E) indices. The main findings include four species namely, Botaurus cinnamomeus (Gmelin, JF, 1789), Lonchura maja (Linnaeus, 1766), Lonchura leucogastroides (Horsfield & Moore, 1856), and Passer montanus (Linnaeus, 1758), with the order Passeriformes dominating abundance (H' = 1.15 at location 1 and 1.09 at location 2, classified as moderate). The low dominance index and high evenness indicate that the community structure is stable, influenced by food availability and minimal human disturbance, although the homogeneity of the habitat in the second location limits diversity. The implications of this study highlight the need for rice field conservation as an urban buffer to prevent the decline of bird biodiversity.